PENGARUH KOMPLEKSITAS TUGAS, INDEPENDENSI, DAN KOMPETENSI TERHADAP KUALITAS AUDIT DENGAN INTEGRITAS AUDITOR SEBAGAI VARIABEL PEMODERASI - Ditha Purnamasari, Pande Putu; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The purpose of this study is to investigate and provide empirical evidence of the effect of task complexity, independence, and competence to audit quality with integrity auditor as moderating variables. This research was conducted in Public Accountant registered in the Bali Provincial Institute of Certified Public Accountants Indonesia. The sampling method used in this research is nonprobability sampling with saturated sampling technique. As the data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). Based on the analysis results obtained addressing that task complexity a significant negative effect on audit quality, independence and competence of positive and significant impact on audit quality, the integrity of the auditor is able to moderate the complexity of the task on the quality of the audit, but the integrity of the auditor is not able to moderate the independence and competence of the audit quality.
Keywords: The Complexity of the Task, Independence, Competence, Integrity Auditor, Quality of Audit